2011
DOI: 10.1002/ptr.3546
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxic Activity and Structure Activity Relationships of Iridoid Glucosides Derived from Veronica species

Abstract: This study was an investigation of the cytotoxic activity of iridoid glucosides, including aucubin, catalpol, 6-O-acetylcatalpol, veronicoside, catalposide, verproside, amphicoside, veratroylcatalposide, verminoside, aquaticosides B and C isolated from different Veronica species. The cytotoxic activity was determined against Hep-2 (human epidermoid carcinoma), RD (human rhabdomyosarcoma), L-20B (transgenic murine L-cells) cancer cell lines and Vero (African green monkey kidney cells) non-cancerous cell line us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…While cytotoxic activity of amphicoside (5) and veronicoside (3) found lower than that of verminoside, 6-O-veratroylcatalposide and verproside were found to have cytostatic activity. Catalpol and aucubin did not show any cytotoxic activity against three of the tested cell lines (Saracoglu et al, 2008;Saracoglu & Harput-Hudaverdi, 2009). Our previous results are in good agreement with present results and could be good explanation of the cytototoxic activity of V. cuneifolia subsp.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…While cytotoxic activity of amphicoside (5) and veronicoside (3) found lower than that of verminoside, 6-O-veratroylcatalposide and verproside were found to have cytostatic activity. Catalpol and aucubin did not show any cytotoxic activity against three of the tested cell lines (Saracoglu et al, 2008;Saracoglu & Harput-Hudaverdi, 2009). Our previous results are in good agreement with present results and could be good explanation of the cytototoxic activity of V. cuneifolia subsp.…”
Section: Discussionmentioning
confidence: 87%
“…cuneifolia showed stronger radical scavenging and cytotoxic activities than V. cymbalaria for all tested concentrations. Cytotoxic activities of aucubin, catalpol, and catalpol derivatives isolated from Veronica species were also determined against Hep-2, RD, and L-20B cell lines, previously (Saracoglu et al, 2008;Saracoglu & Harput-Hudaverdi, 2009). Verminoside (6), the transcaffeic acid ester of catalpol, showed very strong cytotoxicity against tested cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Saracoglu and Harput (2012) showed that some iridoid glucosides of V. anagallis-aquatica , V. persica Poir, and V. thymoides P.H.Davis subsp. pseudocinerea M.A.Fisch.…”
Section: Introductionmentioning
confidence: 99%
“…Plants belonging to the genus Veronica and several of their constituents have shown potent cytotoxic activity on different cell lines (Harput et al, 2002a;Teng et al, 2008;Saracoglu and Harput, 2012). In the present study the V. urticifolia methanolic extract was evaluated for its in vivo antitumor properties.…”
Section: Cytotoxic Activity Against Ehrlich's Tumor Cells In Micementioning
confidence: 92%
“…Regardless of widespread use, mostly as diuretics, for their wound-healing properties and in medical treatment of respiratory diseases, there is a scarcity of physiological evidence to support any claim of therapeutic values for Veronica species. Only few studies confirm that certain Veronica genus reveal considerable bioactivity such as antibacterial (Stojković et al, 2013;Gusev et al, 2012), antioxidant (Živković et al, 2012), anti-inflammatory (Harput et al, 2002a) and cytotoxic (Harput et al, 2002a;Saracoglu and Harput, 2012) activities.…”
mentioning
confidence: 99%